Simulação de atualização de infra-estrutura de redes para suporte a telefonia IP - Canalle, Alexandre (2011)
This research performs an explanatory and applied nature approach of how to simulate the data network infrastructure update to support IP telephony. The main objective is virtually simulate a communication convergence project of a small business that have branches and representatives spread over distant areas and that intend to reduce internal calls costs through the use of IP Telephony.. With the usage of a routers emulation tool that allows to install multimedia services together with the traffic classification and priorization rules configuration, is shown the viability of the simulation previously the applying of productive enviroment changes.. After being utilized experimental and bibliographic research techniques, among the results obtained resides the proving of the IP telephony working installed inside the routers and the efectiveness of classification, marking and traffic priorization to permit the internal communication with the reduced connectivity costs to the matrix, with the maintenance of voice quality perceived on the public switched telephone network.